(untitled) - Lumelsky, Vladimir (Hoboken, NJ)
As the first book fully devoted to robot motion planning in unstructured environments, Sensing, Intelligence, Motion is a must-read for engineers, scientists, and researchers involved in robotics. It will help them migrate robots from highly specialized applications in factories to widespread use in society where autonomous robot motion is needed.
Keywords: Robots,Người máy,Manipulators (Mechanism),Máy móc; Motion,Di chuyển